1997
DOI: 10.1177/107906329700900305
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Delinquents: A Between-Group Comparison Study of Sexual and Nonsexual Offenders

Abstract: This article presents a comprehensive descriptive study of incarcerated juvenile sexual offenders and an analysis of group differences between sexual and nonsexual offenders. The study utilized a large sample (N = 156) with a properly defined comparison group, standardized psychometric measures, and substantial institutional and therapeutic record reviews. The sample was described and compared on measures of delinquent history, intelligence, academic achievement, and psychopathology. The goal of the research w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…I The vast majority of these studies have described outpatient samples with only a few focusing on the incarcerated adolescent sexual offender (Jacobs et al, 1997).…”
Section: N O T E Smentioning
confidence: 99%
“…I The vast majority of these studies have described outpatient samples with only a few focusing on the incarcerated adolescent sexual offender (Jacobs et al, 1997).…”
Section: N O T E Smentioning
confidence: 99%
“…Studies of the relationship between childhood maltreatment and executive functioning have produced a number of interesting findings. While some studies have reported significant associations between these two variables (De Bellis et al, 2009;Spann et al, 2012), others have found no relationship between them (Jacobs, Knnedy, & Meyer 1997;Veneziano, Veneziano, Legrand, & Richards 2004). Studies of children show that the executive components that appear to be most influenced by exposure to maltreatment are working memory, inhibition, verbal attention, processing speed, problem solving, planning, and decision making (Beers & De Bellis, 2002;Fishbein et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, family relationships of juvenile sex offenders appear to be challenged, but may not present greater clinical challenges than do the families of other delinquents. Several uncontrolled studies indicate that adolescent sexual offenders tend to have academic deficits (Awad & Saunders, 1989;Fehrenbach, et al, 1986), and these problems occur at rates similar to the rates of other delinquent youth (Ford & Linney, 1995;Jacobs, Kennedy, & Meyer, 1997). Like family problems, academic problems appear to function as nonspecific delinquency risk factors.…”
Section: Assumption 2: Juvenile Sex Offenders Are Different From Othementioning
confidence: 87%